Membaca Televisi 'ala Al-Jabiri - Ibnu Hamad (Program Studi Ilmu Komunikasi, 2007)
Since the New Order Era collapsed and the Reformasi Era had come out, the media freedom reached its climax. The growth of mass media had increased until the amazing number. Unfortunately, this rapid growth didn't base on the idealism, but only for the business purposes. As a consequence, the TV station owners and investors are only emphasizing how many profit they can get, without considering the importance of qualified content of TV program. This article wants to introduce a reading and making a meaning concept toward the TV program content, which firstly offered by Muhammad Abed Al-Jabiri, an Arabic thinker. In this concept, there are three ways to understand the TV program content, which is bayani, burhani, and irfani. Through these three ways, we could increase the media iiteracy rate in our society, so we could stand at attention wisely toward the content of a TV program.